Castor Oil and PEG-Based Shape Memory Polyurethane Films for Biomedical Applications - BİNGÖL ÖZAKPINAR, ÖZLEM (WILEY, 2014)
A series of polyurethane film were prepared from poly(ethylene glycol) with different molecular weight (PEG 1500, 3000, and 8000) and castor oil by one-shot bulk polymerization method. Hexamethylene diisocyanate and 1,4-buthane diol were used as diisocyanate and chain extender, respectively. In order to characterize the samples, their density, swelling ratio, water contact angle, surface free energy, gel content, thermal, and viscoelastic properties were determined. The effect of the soft segment length (SSL) and hard segment content (HSC) of all polyurethane films on their shape memory behavior such as shape fixity (R-f) and shape recovery (R-r) rates were investigated by bending test. Direct contact and MTT tests were used for assessment of cell adhesion and proliferation. The relatively high R-f and R-r values were obtained for the samples programmed at high temperature difference. R-f increased with decreasing HSC. On the other hand, R-r tended to decrease with increasing SSL. After evaluating experimental data by a nonlinear equation, it was found that HSC is more effective parameter on shape memory property than SSL. The gel content, swelling ratio, and water contact angle of the samples were dependent on both SSL and HSC in their structures. (c) 2014 Wiley Periodicals, Inc.
Keywords: biomaterials; polyurethanes; properties and characterization; WOUND DRESSING APPLICATIONS; POLYMERS; MORPHOLOGY; NETWORKS; PROPERTY; BEHAVIOR; SEGMENTS; SOFT